Basics of communication : a relational perspective / by Steve Duck and David T. McMahan - "Duck, Steve"; McMahan, David T. (New Delhi, 2012)
Key Features Comprehensive, two-chapter coverage of media and relational technology explores the use of mobile devices and social media in daily communication The books refreshing and original approach engages students with lively, topical examples that challenge them and invigorate classroom discussion Listen in on Your Life, Make Your Case, and Strategic Communication boxes get students personally involved with the material About the Book: The Basics of Communication: A RelationalPerspective: 2nd Edition Written in a warm and lively style and packed with learningtools, The Basics of Communication offers an engaging look at theinseparable connection between relationships and communication.Steve Duck and David T. McMahan combine theory and application tointroduce students to fundamental communication concepts. Theirbook also provides practical instruction on communicatinginterpersonally, in groups, in interviews and on making effectivepresentations. The authors encourage students to think critically,to link communication theory to their own experiences, and toimprove their communication skills in the process. New to the Second Edition A new chapter on interviewing covers online job searching,interviewing via video/Skype, and much more Each chapter has been streamlined to further increasereadability, and 42 additional tables help students bettersynthesize the material The books visually dynamic art program has been updated, with 35new photographs Three new pedagogical boxes (Contrarian Challenge, Case inPoint, and College Experience) encourage student engagement withthe content Contents Preface An Overview of Communication Verbal Communication Nonverbal Communication Listening Identities and Perceptions Talk and Interpersonal Relationships Groups and leaders Culture and Communication Technology in Everyday Life Relational Uses and Understanding of Media Preparing for a Public Presentation Developing a Public Presentation Relating Through Informative Speeches and P
Keywords: Communication